Video Games and Stress: How Stress Appraisals and Game Content Affect Cardiovascular and Emotion Outcomes - Porter, Anne Marie; Goolkasian, Paula (Frontiers in Psychology, 2019)
Although previous studies have found that video games induce stress, studies have not typically measured all salient indicators of stress responses including stress appraisals, cardiovascular indicators, and emotion outcomes. The current study used the Biopsychosocial Model of Challenge and Threat (Blascovich & Tomaka, 1996) to determine if video games induce a cardiovascular stress response by comparing the effects of threat and challenge appraisals across two types of video games that have shown different cardiovascular outcomes. Participants received challenge or threat appraisal instructions, and played a fighting game (Mortal Kombat) or a puzzle game (Tetris). Study outcomes were heart rate variability, systolic and diastolic blood pressure, and positive and negative emotion ratings measured before, during and after gameplay. Results indicated that threat appraisal instructions increased negative emotion ratings and decreased heart rate variability, but not blood pressure, which is an essential marker for cardiovascular stress responses. Increased blood pressure and decreased heart rate variability was associated with fighting game players when compared with the puzzle game players, indicating a cardiovascular stress response; however, fighting game players also reported higher positive emotion ratings. Based on the study findings, video games do not induce stress responses like mental stressors used in previous research, demonstrating that the interactive player experience in video gaming may have more complex effects on stress outcomes. Future research should comprehensively measure biopsychosocial stress indicators and multiple emotional states over time to fully examine the relationship between video games and stress.